Echocardiographic evaluation of left-to-right shunt in ventricular septal defect and persistent ductus arteriosus. Issue 3 (March 1977) - Bloom, K R; Rodrigues, L; Swan, E M
Abstract : Forty-five patients with either a ventricular septal defect or a persistent ductus arteriosus were assessed by echocardiography and cardiac catheterisation. Left atrial dimension was expressed either as a function of the body surface area (LAD cm per m2 BSA), or as a multiple of the aortic root dimension (LAD/AR), and was compared with the shunt size as determined by oximetry. A highly significant (P less than 0-001) regression relation was found for the group as a whole. A significant relation also existed for each individual group: ventricular septal defect, ventricular septal defect with pulmonary hypertension, and persistent ductus arteriosus. Regression equations were derived for the whole group. The value of echocardiography is in separating large from small shunts and in adding a dimension to the follow-up of the individual patient.